Letter - Brook, Charles Wortham, 1901-1983
041-0188-001 SPANISH MEDICAL AID COMMITTEE. Hon. Sec. Dr. Charles Brook Tel. Holborn 1207 Kern House 36, Kingsway, W.C.2 10th August 1936. To the Joint Secretary, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Sirs, At a meeting of members of the Socialist Medical Association and of the Inter-Hospital Socialist Society held on Saturday last under the chairmanship of Dr. H.B. Morgan, it was unanimously agreed that medical units should be sent to Spain and a Spanish Medical Aid Committee was constituted with myself as secretary. I was requested to approach you with a view to receiving a deputation from the committee at your earliest convenience in order to discuss the project with you. The deputation will consist of Dr. Morgan, myself and a member of the Inter-Hospital Socialist Association. I may add that we have already a sufficiency of volunteers who are prepared to start for Spain immediately. I should be grateful if you would give this matter your very early attention, and if you will advise by telephone if you will receive this deputation and if so at what time. Yours fraternally, Charles Brook 292/946/41/188